OBJEK PAJAK ASURANSI DAN NON PAJAK ASURANSI STUDI KASUS: ASURANSI PROPERTI KOMERSIAL PERUSAHAAN: PT RITEL SUKSES - Ashaari, Taslam; Irawan, Deni; Vientiany, Dini (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The object of insurance tax includes insurance company profits, such as loss insurance premiums. On the other hand, some types of insurance, such as life and health insurance, often receive special tax treatment or are not even taxed at all. The goal is to encourage people to have long-term financial insurance and ease the burden of health costs. The aim of this research is to gain a deeper understanding of insurance tax objects and non-insurance objects. By using a qualitative methodology with a descriptive analytical approach, this approach was chosen to provide a comprehensive analysis of insurance tax and non-insurance tax objects and their consequences. Insurance premiums, profits from premium reserve investments, other income (commissions, administration fees, etc.), insurance claims received, Value Added Tax (VAT), and Income Tax (PPh) are insurance tax objects, while non-Insurance Tax objects: Insurance Health, Accident Insurance, Life Insurance, Endowment Insurance, Scholarship Insurance.n, dan hasil temuan.